The Effectiveness of the Al-Baghdadi Method in Reciting the Muqatha'ah Letters at the Beginning of the Surah with the Ahkamus Shaut approach - Maman Maman; Muhajir Muhajir; Zakaria Syafe'i (UIN Sunan Gunung Djati Bandung, 2021)
This study aims to explore al-Baghdadi's method of reciting the harfu muqatha'ah at the beginning of the letter. Literature study is the method in this study. The data obtained came from primary and secondary references, such as books and journals of national and international repute that studied the ahkamus shaut, harfu muqatha'ah, and the al-Baghdadi method. The data collection method used content analysis techniques. The study steps taken include editing, organizing, and inference. The results of the study show that the al-Baghdadi method is empirically able to have a significant impact on the students' ability to read the Qur'an, and the pronunciation of the muqatha'ah letters at the beginning of the letter is also an inseparable part of the effectiveness of the use of the al-Baghdadi method. The study recommends that teachers use the al-Baghdadi method in teaching their students how to read the Qur'an.